2005
DOI: 10.1007/bf03022050
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced central organ oxygenation after application of bovine cell-free hemoglobin HBOC-201

Abstract: In the present animal model, IHD with Ringer's solution and additional application of HBOC-201 increased oxygen extraction and tpO(2) in the liver and skeletal muscle, in parallel and in comparison with baseline values and a control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…8 Standl et al showed preservation of skeletal muscle oxygenation in dogs. 9 Thus the data from Freitag et al 1 are consistent with observations previously made in normovolemic anemia and extends our understanding by employing a larger animal (dog) and a different HBOC (Hemopure). A common observation in all of these studies is an increase in blood pressure and in systemic vascular resistance.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…8 Standl et al showed preservation of skeletal muscle oxygenation in dogs. 9 Thus the data from Freitag et al 1 are consistent with observations previously made in normovolemic anemia and extends our understanding by employing a larger animal (dog) and a different HBOC (Hemopure). A common observation in all of these studies is an increase in blood pressure and in systemic vascular resistance.…”
supporting
confidence: 87%
“…As demonstrated by Freitag et al, 1 systemic vascular resistance falls, cardiac output increases, and blood pressure may fall. In either case, oxygenation is preserved, at least initially, by increasing oxygen extraction as the hemoglobin concentration falls.…”
mentioning
confidence: 87%
“…Our experimental model was developed to obtain a total volume exchange that mimicked previously published articles wherein hemorrhage or isovolemic hemodilution was carried out to remove 50% of the animals total blood volume or attain a cumulative 50% volume exchange. 46, 911 These earlier studies suggested that this “stress” would result in the development of a metabolic acidosis (lactic acidosis) presumably from inadequate oxygen delivery or maldistribution of blood flow and low tissue oxygen tension. A recent study, using an experimental design similar to the current study, however, suggested that physiologic coupling of oxygen delivery and consumption after administration of HBOC-201 is not impaired.…”
Section: Discussionmentioning
confidence: 99%
“…Our data indicate that the positive effect on cold preservation-reperfusion injury is based on an improved organ oxygenation and the hemoglobin mediated induction of HO-1, which increases the biliverdin and bilirubin production, being important antioxidants by acting as intracellular radical scavengers [31,32]. Previous studies already showed that HbG 200 promotes O 2 unloading due to low oxygen affinity, increases tissue oxygen tension, and finally improves organ oxygenation, despite temporary negative effects on microcirculatory flow [20,33,34].…”
Section: Discussionmentioning
confidence: 71%
“…Recently Freitag et al demonstrated in an animal model of isovolemic hemodilution an increased oxygen tension (tpO 2 ) and an improvement of tissue oxygenation in the liver and skeletal muscle [20]. In several models of hemorrhagic shock an improved outcome after HBOC application could be demonstrated [21][22][23].…”
Section: Introductionmentioning
confidence: 98%